Clive Hamilton - Hamilton, Clive (Melbourne : Clive Hamilton, 2008)
Blog on global warming written by the Melbourne-based Clive Hamilton.
Title from title screen (viewed on 19 March 2010).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.clivehamilton.net.au
System requirements: Adobe Acrobat reader required to view/print pdf files.
Selected for archiving
Keywords: Blogs -- Australia; Climatic changes -- Social aspects